Sistema de gestão de acesso usando reconhecimento facial e microcomputador - Franklin, Luis Antônio Viana (2024)
Technology has been advancing rapidly, increasingly permeating people’s daily lives and facilita- ting human life through process automation. A notable example is the use of facial recognition for access control, increasing security in various areas. However, despite significant advances, there are still challenges to be overcome. Variations in lighting, facial expressions, and occlusions are some of the obstacles that still need to be overcome to improve the effectiveness and accuracy of these systems. Therefore, it is crucial to deepen the study of these challenges and the techniques used in facial recognition. Currently, access management at the Innovative Technologies Laboratory (LTI) presents opportunities for improvement. The manual registration of the name and the time of withdrawal and return of the key is a process that can be optimized. In this sense, the development of an automated facial recognition system can make this process more efficient and secure. Based on this, this work proposes the development of an access management system for the laboratories of the Federal University of Ceará - Russas Campus, using Microcomputer and Computer Vision for facial recognition. It is expected that this system will make access management more efficient, facilitating student access and teacher management. This is an important step towards more modern and efficient laboratory management.